Predictors of survival in neurometastatic Merkel cell carcinoma. (September 2018) - Harary, Maya; Kavouridis, Vasileios K.; Thakuria, Manisha; Smith, Timothy R.
Abstract: Background: Merkel cell carcinoma (MCC) is a rare cutaneous malignancy of neuroendocrine origin, with about 30 cases of brain metastasis (BM) reported in the literature. Historically, the treatment of neurometastatic MCC has largely included chemotherapy and radiotherapy. The aim was to investigate predictors of overall survival (OS) in neurometastatic MCC. Methods: In this retrospective study, we surveyed institutional databases and conducted a systematic review of the literature to identify cases reporting on management of distant MCC BM. A pooled survival analysis was performed on the institutional and literature cases to assess predictors of OS. Results: Forty cases were included for analysis, describing operative [14] and non-operative [26] management. Median time to central nervous system involvement was 17.0-mos (interquartile range 10.5–26.5), and most patients had a single BM (62.5%). Management of intracranial disease included radiotherapy (82.5%), systemic therapy (59.5%) and surgical resection (35%). Operative management was associated with a lower intracranial burden of disease (BoD), but similar systemic BoD. Both neurosurgery (hazard ratio [HR] 0.18, 95% confidence interval [CI]: 0.06–0.54, p = 0.002), having RT (HR 0.37, 95% CI: 0.14:0.93, p = 0.04) and having a single BM (extensive intracranial BoD: HR 2.51, 95% CI: 1.12–5.6, p = 0.03) conferred an OS benefit on risk-unadjusted analysis. Only, neurosurgical resection was an independent predictor of OS (HR 0.12, 95% CI: 0.03–0.49, p = 0.003), controlling for age, BoD and radiotherapy. Conclusions: Resection of MCC BM may confer a survival benefit given appropriate patient selection. Prospective investigation of multimodal management of neurometastatic MCC is warranted, especially given the promise of new immunotherapy agents in treating MCC. Highlights: Merkel cell carcinoma (MCC) is a rare neuroendocrine cancer. Patients who undergo neurosurgical resection of MCC brain metastases may live longer. Multimodal management of neurometastatic MCC may be beneficial.